Die belang van Prof. F.J. van Zyl vir Hervormde Teologie - Beyers, Jaco (HTS teologiese studies, 2017)
In this article the contribution of professor Frans J. van Zyl (1913–2008) will be scrutinised as to determine the influence his thoughts had on the theology of the Netherdutch Reformed Church. As Van Zyl was seen as a follower of the theology of Karl Barth, his greatest influence centered around the ideas of Barth. Here, particular reference will be made to his view of the Bible and the Dialectical theology. The article also addresses the problem of the existence of so-called churchly theology and investigates the role Reformed theology played in the Netherdutch Reformed Church. The contribution Van Zyl made to Reformed theology is measured in terms of his contribution to (1) an understanding of God, (2) to a view on scripture and (3) his emphasis on the importance of mission work. Further, (4) his way of unselfishly serving in the church becomes a theological testimony to his character and example to the church. Lastly, (5) his condonation of white-only membership of the Netherdutch Reformed Church is not seen as a blemish to his name, but rather interpreted here as a continuation of the Reformed heritage in the sense that the nature of man is flawed by sin.